Metric precision via soft-tissue landmarks in three-dimensional structured-light scans of human faces - Fink, Martin; Medelnik, Juergen; Strobel, Karin; Hirschfelder, Ursula; Hofmann, Elisabeth (Journal of Orofacial Orthopedics / Fortschritte der Kieferorthopädie, 2014)
The goal of the current work was to investigate the suitability of ten facial soft-tissue landmarks (trichion, glabella, nasion, left and right orbital, subnasal, left and right porion, pogonion, gnathion) as reference points for metric facial analysis by analyzing their intra- and interserial precision in all three dimensions.The faces of 32 volunteers were scanned using a standardized protocol with a structured-light scanner (FaceSCAN(3D) Scientific Photolab 60 Hz; 3D Shape, Erlangen, Germany). Three examiners placed the landmarks twice within a 2-week interval. Image processing (Onyx Ceph(3); Image Instruments; Chemnitz, Germany) and statistical (SAS 9.2; SAS Institute, Cary, NC, USA) software was used for analysis. All measurements were corrected for mean values per patient and analyzed for intraserial and interserial error by model II ANOVA for a simple classification with random effects.Median intraserial precision was 0.40 mm (range 0.05-1.01 mm) overall, including 0.40 mm (0.33-0.85 mm) on the x-axis, 0.64 mm (0.36-0.87 mm) on the y-axis, and 0.27 mm (0.05-1.01 mm) on the z-axis. Interserial precision was substantially lower at a median of 0.05 mm (0-0.22 mm), often not statistically assessable with intraserial precision. We observed no landmark-associated differences; in particular, the medians of the bilateral landmarks orbital (intraserial: 0.40 mm; interserial: 0.02 mm) and porion (intraserial: 0.36 mm; interserial: small and not assessable) were in the middle of the range of our results. Trichion (intraserial: 0.73 mm; interserial: 0.05 mm) and gnathion (intraserial: 0.87 mm; interserial: 0.20 mm) revealed the highest degrees of intraserial measurement imprecision. Outliers were identified in 1.2% (64 of 5400) of measurements.All selected landmarks offer suitably high levels of intra- and interserial precision for the three-dimensional (3D) metric assessment of facial soft-tissue parameters. No difference between (bi)lateral and facial midline landmarks was noted.
EVALuna2:24844